Kebijakan Penggunaan Sanksi Pidana Dalam Peraturan Daerah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The utilization policy of criminal law sanction in the region regulations can be justified in the criminal law. These are necessary to be learned from the penal policy, because the criminal law sanction has weakness. This research has two purposes. First, to know the consideration of the utilization policy of criminal law sanction in the region regulations. Second, to know the formulation of the utilization policy of criminal law sanction in the region regulations. The research is done by the library study and the field study. The purpose of the library study is to get the secondary data by using documentary study, whereas the purpose of the field study is to get the primary data by using interview guidelines. The analysis of the data uses the qualitative method. The results of the research show that there are no consideration of the utilization policy of criminal law sanction in the region regulations. The consideration of the utilization policy of criminal law sanction in the region regulations is based on the implementation of the higher laws, especially number 22, year 1999. also shows that the formulation of the utilization policy of criminal law sanction in the region regulations has followed the higher laws. Nevertheless, there is one region regulation against the higher laws in the formulation of the criminal law sanction.